Intersecting Inequalities in Romanian Crime Series Shadows (HBO). Expressions of Identity between Authenticity, Stereotypes and “Eastploitation” - Roxana Eichel (Caietele Echinox, 2022)
The representations of gender, ethnicity and class play a particularly significant part in structuring the way in which East European crime fiction makes sense of its cultural identity. Issues of social inequality and discrimination are addressed by the European institutions through the promotion of inter- and multi-cultural values that are meant to foster awareness about social stereotypes and prejudices and promote the artistic expression of more balanced representations (i.e. the EIGE policies). Yet sometimes the gap between the inclusive aims pursued by the European policies and the realities represented in crime films, TV dramas and novels is more than noticeable. This article aims to discuss this fluctuation between disparity, stereotypization, realism and exploitation in the HBO production Shadows (Umbre, 2014-2019).